(untitled) ("Temas Sociais" Journal, 2023)
We approach Mª Leonor Sampaio Botelho (1915-1996), as a social worker, trained at the Institute of Social Service, who went through 4 different political regimes: the end of the 1st Republic and the Military Dictatorship; Salazar period; Marcelist period; and after April 25th. The purpose is to analyze hermeneutically, based on documentary sources and contextualized in time and historical era, her social action. many institutions and bodies. Throughout her intervention, at a time when women’s access to society was impeded by the rules of the regime, she fought for the protection of women at work and other modern assistance measures, especially when she was a deputy. He was an uncomfortable voice within the Salazar regime, but, naturally, he never questioned it, despite some disappointments in terms of social policy during the Salazar period.